Productive Zakat for Community Empowerment: an Indonesian Context - Urwatul Wutsqah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
Indonesia is the largest Moslem country in the world. Paying zakat apart from being a means for Muslims to worship, zakat can also become a pillar of the people's economy when the zakat funds are properly managed and handed over to an amil zakat agency, amil zakat institution or an official baitul mal from the government, where if we look at the potential for raising funds Zakat to be managed productively has very good prospects for the economic progress of the people who are included in the category of entitled to receive assistance from this zakat fund. Therefore, the author here examines through this research using a qualitative descriptive method with data collection techniques in the form of documents, such as books or laws and regulations. This research is expected to provide a little knowledge benefit to readers in order to optimize the management of zakat funds into productive zakat which is one of our efforts to improve the level of the community's economy, the author sees that if zakat is managed productively, it can be maximized both in its management and use by the parties. related to being able to make people free from poverty and ignorance so that people who were initially in a mustahik condition so that they rose to become muzakki.